The Economic Policy Peculiarities of the "Historical Right" Governments of the Kingdom of Italy (1861–1876) - Михайленко, М. (Київський національний університет імені Тараса Шевченка, 2018)
This research analyses the economic policies peculiarities of the "historical right" governments of the Kingdom of Italy from the first stage of the unification of this country into a single nation state and rise of the "historical right" governments to power till the transfer of power to the "historical left". It also specifies the main directions of economic reforms in a certain period of time and their impact on the further development of the state. The research establishes that the liberal economic model for country's development chosen by its leadership at the very beginning allowed to quickly create the domestic market of goods and services, establish fruitful foreign economic relations with the greatest economic powers of that time and attract foreign investments into the Kingdom, promoting the development of the Kingdom's agricultural sector and accumulating a substantial capital within the country. However, given the significant economic backwardness of the states of the Apennine peninsula before the unification and the actual abolition of customs barriers in trade with more powerful European countries after 1861, it had a negative impact on the country's weak industry and deepened the distortion of development along the north-south line. The undeniable achievement of the "historical right" governments in the fiscal policy was the overcoming of the huge deficit of the state budget before 1876.

Здійснено аналіз економічної політики Королівства Італія протягом періоду правління "історично правих" урядів після завершення його об'єднання в єдину національну державу. Охарактеризовано основні напрямки економічних реформ у визначений період та їхній вплив на подальший розвиток держави. У результаті дослідження показано, що обрання керівництвом країни ліберальної економічної моделі на початку існування держави дозволило достатньо швидко створити внутрішній ринок товарів та послуг, активізувати зовнішньоекономічні зв'язки з найбільшими економічними потугами того часу, сприяти розвитку сільськогосподарського сектору економіки, забезпечити накопичення капіталу всередині країни та залучити зовнішні інвестиції в королівство. Водночас, з огляду на значну економічну відсталість держав Апеннінського півострова напередодні об'єднання, фактичне скасування митних бар'єрів у торгівлі з більш потужними європейськими країнами після 1861 р. завдало удару слабкій промисловості країни та поглибило нерівномірність її розвитку за лінією північ-південь. Беззаперечним досягненням "історично правих" урядів у сфері бюджетної політики стало подолання величезного дефіциту державного бюджету до 1876 р.
Особливості економічної політики перших "історично правих" урядів Королівства Італія (1861-1876 рр.)
Keywords: Kingdom of Italy; liberal economic policy; the "historical right" governments; customs barriers; tax policy; protectionism; Королівство Італія; ліберальна економічна політика; "історично праві" уряди; митні бар'єри; податкова політика; протекціонізм